Mining the Desert Margins: Exploring the Territorial and Organizational Dynamics of Artisanal Mining in Namibia - Antoine Latarge; Hugo Quemin; Kaarina Efraim; Marie Forget; Mélanie Duval (EchoGéo, 2025)
This article examines the social and spatial organization of artisanal gemstone mining in Namibia, shedding light on a largely under-researched area. It delves into the power dynamics and experiences of precarity faced by miners, highlighting the associative strategies they employ daily. These strategies are shown to be responses to specific situations, shaped by various factors, with the miners' agency playing a significant yet not dominant role. Drawing on fieldwork conducted at two major artisanal mining sites in Namibia, Xoboxobos and Tubusis, the article utilizes semi-structured interviews and participant observation to propose a typology of associative modes, identifying the influential factors and organizational choices of the miners. By providing a comprehensive overview, this article paves the way for future research on the artisanal mining sector in Namibia, opening new dimensions and perspectives.